Streaming video based on temporal frame transcoding - Fadlallah , Fadlallah Ali; Khalifa, Othman Omran; Hassan Abdalla Hashim, Aisha (IJISET, 2016)
In a previous couple of years different types of interactive and multimedia services are appeared such as distance learning, video conferencing, video telephony and others, which are used as one of the best means of communication in everyday life, for work or practical purpose. However, the most challenging task is to deliver these services in a different quality for users who have different hardware capabilities (processing, display, decoder, memory, etc.) interconnected via a heterogeneous network. One of the most problematic network services is a video streaming. The video streaming consumes a lot of network bandwidth and any loss or delay of the data affecting the video quality. Hence, transcoding technology is required to adjust and reduce the constraints of the network and user terminal. This paper is proposed a new video streaming technique to reduce the number of video frames that you need to send across networks. By employing Smart Frame Skipping Module (SFSM) to skips some frames of video in the server and sent the adapted video stream while receiving video the client will re-construct the frames which skipped of the video in the server. Also, to test and evaluate the proposal flexibility and adaptability the operational parameters were used with different values applied to the samples videos.